A Programmable Programming Language. - FELLEISEN, MATTHIAS; FINDLER, ROBERT BRUCE; FLATT, MATTHEW; KRISHNAMURTHI, SHRIRAM; BARZILAY, ELI; MCCARTHY, JAY; TOBIN-HOCHSTADT, SAM (Communications of the ACM, 2018)
The authors discuss the development of the Racket programming language. They mention the use of embedded domain-specific languages (eDSLs), the need to develop a language that can easily create these eDSLs, and the long-range prospects and problems of language-oriented programming (LOP).